Type 2 Diabetes and Myocardial Infarction: Recent Clinical Evidence and Perspective - Cui, Jing; Liu, Yanfei; Li, Yiwen; Xu, Fengqin; Liu, Yue (Frontiers in Cardiovascular Medicine, 2021)
Type 2 diabetes mellitus (T2DM) and its complications are seriously affecting public health worldwide. Myocardial infarction (MI) is the primary cause of death in patients with T2DM. T2DM patients without a history of coronary artery disease (CAD) have the same risk of major coronary events as those with CAD, T2DM patients with a history of MI have >40% risk of Reoccurrence of MI. Thus, CAD in patients with T2DM needs to be treated actively to reduce the risk of MI. The cardiology community focussed on the role of T2DM in the development of CAD, and on the related issues of T2DM and MI with respect to comorbidities, prognosis, drug therapy, and heredity. In this mini review, the latest progress of clinical evidence-based research on T2DM and MI in recent years was reviewed, and the possible research directions in this field were considered and prospected.